Interaction of Physics Teachers with their Students in the Use of ICTs in Teaching Elementary Particle Physics Through Digital Games (Research, Society and Development, 2022)
The teaching of Elementary Particle Physics (EPF), with the scarcity of didactic materials of Modern and Contemporary Physics in high school, we realized the need to develop a didactic sequence with the support of Information and Communication Technologies (ICTs), in learning based on in digital games. The teaching of physics was already very complicated for some students, with a poor understanding of the subject and its constant presence in the school routine. Currently, students of this generation, known as digital natives, live in a highly technological reality, with access to digital games in different ways. However, teachers must be inserted in this context, because this population plays in different styles, such as: RPG (Role-Playing Game), adventure, sport, strategy. Therefore, teachers must have knowledge not only of the subject taught, but also of the way in which these games work, in this way, passing on to the student the knowledge of FPE, through a language close to the student, facilitating the engagement for their learning, motivating them to knowledge and fun. Revision bibliographic study, as well as an exploratory study of research and activities already carried out in some public education institutions in Brazil. It was concluded that ICTs are present in the school routine, with the need for teachers to be increasingly updated, ahead of their students, with a view to offering teaching and learning in an easy, comprehensive, joyful way, making students have greater interest in the subject studied, through digital games, in order to demonstrate this methodology as a great potential, differentiating the methods already used.